Association between periductal fibrosis and bile duct dilatation among a population at high risk of cholangiocarcinoma: a cross-sectional study of cholangiocarcinoma screening in Northeast Thailand. Issue 3 (20th March 2019) - Chamadol, Nittaya; Khuntikeo, Narong; Thinkhamrop, Bandit; Thinkhamrop, Kavin; Suwannatrai, Apiporn T; Kelly, Matthew; Promthet, Supannee
Abstract : Objectives: To assess associations between periductal fibrosis (PDF) and bile duct dilatation (BDD) in ultrasonography (US) screening of population at risk of cholangiocarcinoma (CCA) due to residence in an endemic area for Opisthorchis viverrini. CCA survival rates are low, and early identification of risk factors is essential. BDD is one symptom that can identify patients at risk of CCA. Detection of PDF by US can also identify at-risk patients, at an earlier stage of CCA development. Identification of association between PDF and BDD will inform screening practices for CCA risk, by increasing the viability of PDF screening for CCA risk. Setting: Nine tertiary care hospitals in Northeast Thailand. Design: Cross-sectional study. Participants: Study subjects in the Cholangiocarcinoma Screening and Care Program (CASCAP) in Northeast Thailand. CASCAP inclusion criteria are all residents of Northeast Thailand aged ≥40 years. Participants are recruited through CCA screening centres and through primary healthcare units. So far, 394 026 have been enrolled. Methods: PDF and BDD were identified through US. PDF was categorised into three groups, PDF1, 2 and 3, depending on their high echo locality in the peripheral, segmental and main bile duct, respectively. Associations between PDF and BDD were determined by adjusted OR and 95% CI using multiple logistic regression. Results: BDD was found in 6.6% of PDF3, 1.7% of PDF2 and 1.4% of PDF1 cases. Among PDF cases, especially in PDF3, BDD was found in men more than in women (8.9% and 4.6%, respectively). Compared with non-PDF, the association between PDF3 and BDD was highly significant (adjusted OR=5.74, 95% CI 4.57 to 7.21, p<0.001). Conclusions: Our findings reveal that there is a relationship between PDF and BDD, which is associated with CCA. Therefore, PDF can also be an indicator for suspected CCA diagnosis through US.